Improving the quality of dairy sauces by using condensed low-lactose milk whey. - Honchar, Yuliia; Гончар, Юлія Миколаївна; Gnitsevych, Victoriya (Tallinn: Scientific Route OÜ, 2024)
ENG :For optimal functioning of all organs and systems in the human body, nutrition must be complete and balanced. This is achieved by improving recipes and produc tion technologies of existing food products to preserve their nutritional properties or provide them with new properties. In the presence of associated diseases, espe cially food allergies, malabsorption or even intolerance to certain food substances, the existing range of food products should be expanded by developing technolo gies for special nutrition. Mayonnaise products, popular among consumers but not highly biologically valuable or balanced, cannot be included in the diet of individuals allergic to egg products. There have been efforts to replace egg ingredients in mayon naise with plant-based proteins, but whey proteins in mayonnaise products have not received enough attention. Although secondary dairy raw material – milk whey is a valuable and cost-effective resource that must be processed, searching for its applications is ongoing. Additionally, mayonnaise products based on whey can not only expand the range of sauces for people allergic to eggs but also serve as a source of animal proteins for lactose-intolerant individuals after lactose removal. This new direction of its use is crucial because previous studies have shown that excluding lactose-containing foods from the diet or partially restricting them does not improve human health. This issue can be addressed using low-lactose protein-carbohydrate dairy raw materials – processed milk whey. This chapter of the monograph presents research results on the possibility of using fermented mashed pumpkin pulp (FMPP) with a high content of pectin and condensed in vacuo low lactose milk whey (CLLW) in emulsion sauces similar to mayon naise. Rational oil emulsification parameters have been established, and the characte ristics of model samples using FMPP and CLLW in different ratios have been studied. The quality of sauces with an emulsified oil volume of 60 % has been evaluated. o establish the rational ratio of main components in the semi-finished product, the rheological properties of model systems have been studied, including their in fluence on the formation of structuring indicators, such as emulsifying properties. The possibility of using a protein-carbohydrate semi-finished product (SFLLW) based on CLLW and FMPP as a base for emulsion-type sauces like mayonnaise has been demonstrated.///////////////////////UKR : У цьому розділі монографії представлено дослідження використання ферментованої протертої м’якоті гарбуза з високим вмістом пектину та згущеної низьколактозної молочної сироватки в емульсійних соусах, подібних до майонезу. У дослідженні встановлюються раціональні параметри емульгування олії та досліджуються модельні зразки із змінним співвідношенням ферментованого протертого гарбузового м’якоті та згущеної низьколактозної молочної сироватки.
Підвищення якості молочних соусів шляхом використання згущеної низьколактозної молочної сироватки.
Keywords: Sauce; emulsification; mayonnaise; lactose ance; lactose malabsorption; egg-free sauce; milk whey; condensed in vacuo low lactose milk whey